Improving Veterinary Team Handovers using video reflexive techniques: Presenter(s): Elly Russell, University Of Lincoln/ Veterinary Defence Society, United Kingdom. (April 2023) - Mossop, Liz; Oxtoby, Catherine; Forbes, Ellie
Abstract : Background: Interprofessional communication failures are identified as a contributory factor in adverse events in healthcare (1). Handover practices are an important focus for improvement activities aimed at mitigating this risk (2). Video reflexive ethnography (VRE) has been used to improve handovers in ICU (3) and maternity teams (4). Poor interprofessional communication within veterinary teams can contribute to mistakes, including patient harm, in veterinary practice (5, 6). This research explores how VRE can be applied to improving veterinary team handovers. Methods: Video reflexive ethnography is a novel participatory action research approach. It involves capturing video footage of normal everyday work 'in situ'. Short clips of that footage are shown to teams in reflexive sessions that explore work practices, identifying opportunities for improvement (7). In this study, footage of ICU morning handover in a small animal referral hospital was used in 6 reflexive sessions through which plans for a restructured handover process were developed. Findings: 21 participants took part in 6 reflexive sessions and 3 follow up interviews were conducted. Thematic analysis of audio transcripts of reflexive sessions and interviews was used to explore the acceptability and feasibility of using VRE in a veterinary setting. This analysis identified 3 organisational level moderators (resources, leadership, and practice 'fit') and 3 individual level moderators (self-efficacy, orientation to quality improvement and psychological safety) of VRE acceptability and utility in this practice setting. Discussion: Interventions to assist clinical handovers often focus on standardisation of information transfer, however organisational, cultural and environmental factors also impact handover success (8). Improvement Methods: that embrace the complexity of handover activity, rather than focus solely on standardisation are needed (9). VRE is a useful methodology for generating context-sensitive improvement interventions (10). This study identifies important considerations for applying VRE effectively in veterinary settings. Ethical Approval -University of Lincoln Human Ethics Committee: 3807.